Speech by the Minister for Foreign Affairs of Finland - Pekka Haavisto (Journal of Autonomy and Security Studies, 2022)
Speech by the Minister for Foriegn Affairs of Finland at the Åland Parliament Conference 'The demilitarisation and neutralisation of Åland, a stabilising force for peace in the region'